2021
DOI: 10.3390/pathogens10050502
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Bovine Major Histocompatibility Complex Class II DRB3 Alleles for Perinatal Transmission of Bovine Leukemia Virus

Abstract: Perinatal transmission plays a critical role in the spread of bovine leukemia virus (BLV) infection in cattle herds. In the Holstein breed, we previously identified BLV resistant and susceptible bovine leukocyte antigen (BoLA)-DRB3 alleles, including BoLA-DRB3*009:02 and *014:01:01 with a low BLV proviral load (PVL), and *015:01 and *012:01 with a high PVL. Here, we evaluated the perinatal BLV transmission risk in dams with different BoLA-DRB3 alleles. BoLA-DRB3 alleles of 120 dam-calf pairs from five dairy fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…BLVinfected susceptible cattle were found to have a significantly higher risk of horizontal transmission. Similarly, vertical transmission risk and horizontal transmission appeared to be extremely high for dams and cattle with susceptible alleles compared to those with resistant alleles [49]. In contrast, the resistant BoLA-DRB3 allele can effectively inhibit or prevent BLV infection, as observed in this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…BLVinfected susceptible cattle were found to have a significantly higher risk of horizontal transmission. Similarly, vertical transmission risk and horizontal transmission appeared to be extremely high for dams and cattle with susceptible alleles compared to those with resistant alleles [49]. In contrast, the resistant BoLA-DRB3 allele can effectively inhibit or prevent BLV infection, as observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, BLV-infected resistant cattle are low risk of BLV transmission because of weak BLV infection with low PVL. In addition, PVL was maintained at low level in most dams with resistant alleles, thereby reducing the risk of vertical BLV transmission [49]. In contrast, BLV-infected susceptible cattle are at a high risk of BLV infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results confirm that milk from susceptible BLV-infected dams has a higher risk of vertical transmission than that from resistant dams. Similarly, a previous study reported that perinatal transmission risk was markedly low for dams and calves carrying resistant alleles compared to those harboring susceptible alleles [18]. In addition, BLV-infected susceptible cattle were at a higher risk of horizontal transmission risk was reportedly high in BLV-infected susceptible dams with high infection severity and high PVL in blood compared to those with low infection severity and low PVL in blood [26].…”
Section: Discussionmentioning
confidence: 75%
“…Horizontal transmission, which refers to the spread of BLV through blood containing infected cells, can occur through repeated use of syringes and gloves for rectal examinations, dehorning, and castration as well as through blood-sucking insects [11][12][13]. Vertical transmission occurs via dam-calf contact through intrauterine infection of the fetus and/or ingestion of milk and colostrum from BLV-infected dams [14][15][16][17][18]. We previously reported that BLV-infected cells are infectious in milk [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation